Anharmonic Effect Study of Formaldehyde Unimolecular Reaction - Shao1, Y.; Mao2, Y.C.; Yao1, L. (Asian Journal of Chemistry, 2014)
The rate constants of the unimolecular dissociation and isomerization reactions of the formaldehyde were calculated based on the harmonic and anharmonic oscillator models. The anharmonic effect was examined. ab initio Calculations were carried out at MP2/aug-cc-pVTZ level. The results show that the rate constant for the H elimination is the largest, i.e. the H-elimination is predominant channel for unimolecular reaction of HCHO. In addition, in the canonical system, the anharmonic effect is not obvious while, the one is visible in the microcanonical case. It is indicated that the anharmonic Rice-Ramsperger-Kassel-Marcus theory can provide a reasonably good description for formaldehyde unimolecular reaction.